Challenges in Diagnosis of Pseudo Vasa Previa - Etsuko Kajimoto; Shinya Matsuzaki; Satoko Matsuzaki; Yusuke Tanaka; Yukiko Kinugasa-Taniguchi; Kazuya Mimura; Takeshi Kanagawa; Tadashi Kimura (Case Reports in Obstetrics and Gynecology)
Vasa previa is a rare but clinically important obstetrical complication that can be associated with a low-lying placenta or placenta previa. We aim to convey the challenges in diagnosing this condition by presenting 2 cases of pseudo vasa previa diagnosed antenatally as vasa previa using standard and color Doppler ultrasonography. Both patients were falsely diagnosed; only a low-lying placenta was revealed after delivery. These reports emphasize that accurate identification of vasa previa on cervical imaging is important for determining an appropriate treatment strategy.